2012
DOI: 10.4081/ejh.2012.e33
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and biological characterization of chicken amnion epithelial cells

Abstract: Amniotic epithelial cells (AECs) express Oct4, Nanog and Sox-2, which are necessary for maintaining the undifferentiated state of pluripotent stem cells. AECs additionally express CK19, which is a specific marker of epithelial cells, both in vivo and in vitro. In this research, we investigated the biological characteristics and potential for cell therapy of AECs from 6-day-old chicken embryos. We induced the AECs to differentiate into pancreatic islet-like cells (endoderm), adipocytes and osteoblasts (mesoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
(20 reference statements)
5
13
0
1
Order By: Relevance
“…It is a well-known fact that mixed population of cells cultured from amniotic membrane in many species such as human, ovine, chicken, rat, equine and canine also displayed heterogeneous cell population (Marcus et al 2008;Mauro et al 2010;Bacenkova et al 2011;Coli et al 2011;Gao et al 2012;Park et al 2012). In agreement with these reports, it was observed that cultured cells exhibited both spindleshaped fibroblasts and polygonal shaped epithelial cell-like morphology in vitro.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is a well-known fact that mixed population of cells cultured from amniotic membrane in many species such as human, ovine, chicken, rat, equine and canine also displayed heterogeneous cell population (Marcus et al 2008;Mauro et al 2010;Bacenkova et al 2011;Coli et al 2011;Gao et al 2012;Park et al 2012). In agreement with these reports, it was observed that cultured cells exhibited both spindleshaped fibroblasts and polygonal shaped epithelial cell-like morphology in vitro.…”
Section: Discussionsupporting
confidence: 79%
“…These results indicate that these cells were in an undifferentiated state. Expression of these pluripotency marker genes has previously been reported in amnion-derived cells of various mammalian species including rat (Marcus et al 2008), canine (Park et al 2012) and chicken (Gao et al 2012). In addition, reverse transcriptase PCR results indicated that AMSCs expressed the mesenchymal stem cells markers CD44 and CD29, but not haematopoietic surface markers such as CD34 as reported earlier in bovine .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…33 AMSCs are multipotent cells and express transcription factors which are essential for maintaining the self-renewal and undifferentiated state (Table 1). AMSCs are able to give rise into osteoblasts, adipocytes, myocardial cells, 34 neural-like cells, and islet like cells.…”
Section: Avian Amniotic Mesenchymal Stem Cellsmentioning
confidence: 99%
“…AMSCs are able to give rise into osteoblasts, adipocytes, myocardial cells, 34 neural-like cells, and islet like cells. 33 AMSCs suitable tool for tissue engineering research and autologous cell therapy. [34][35][36] Avian cartilage stem/progenitor cells Avian cartilage-derived stem/progenitor cells (CSPCs) were obtained from the surface zone of articular cartilage from 20days old chicken embryo.…”
Section: Avian Amniotic Mesenchymal Stem Cellsmentioning
confidence: 99%